Enhanced Local Skeletal Muscle Oxidative Capacity and Microvascular Blood Flow Following 7-Day Ischemic Preconditioning in Healthy Humans - Jeffries, Owen; Waldron, Mark; Pattison, John R.; Patterson, Stephen D. (Frontiers in Physiology, 2018)
Ischaemic preconditioning (IPC), which involves intermittent periods of ischaemia followed by reperfusion, is an effective clinical intervention that reduces the risk of myocardial injury and confers ischaemic tolerance to skeletal muscle. Repeated bouts of IPC have been shown to stimulate long term changes vascular function, however it is unclear what metabolic adaptations may occur locally in the muscle. Therefore, we investigated seven days of bilateral lower limb IPC (4 x 5-min) above limb occlusion pressure (220 mmHg; n = 10), or sham (20 mmHg; n = 10), on local muscle oxidative capacity and microvascular blood flow. Oxidative capacity was measured using near-infrared spectroscopy (NIRS) during repeated short duration arterial occlusions (300 mmHg). Microvascular blood flow was assessed during the recovery from submaximal isometric plantar flexion exercises at 40 and 60 % of maximal voluntary contraction (MVC). Following the intervention period, beyond the late phase of protection (72-h), muscle oxidative recovery kinetics were speeded by 13 % (rate constant pre 2.89 ± 0.47 min-1 v.s. post 3.32 ± 0.69 min-1; P < 0.05) and resting muscle oxygen consumption (mO2) was reduced by 16.4 % (pre 0.39 ± 0.16 %.s-1 v.s. post 0.33 ± 0.14 %.s-1; P < 0.05). During exercise, changes in deoxygenated haemoglobin (HHb) from rest to steady state were reduced at 40 and 60 % MVC (16 % and 12 %, respectively, P < 0.05) despite similar measures of total haemoglobin (tHb). At the cessation of exercise, the time constant for recovery in oxygenated haemoglobin (O2Hb) was accelerated at 40 and 60 % MVC (by 33 % and 43 %, respectively) suggesting enhanced reoxygenation in the muscle. No changes were reported for systemic measures of resting heart rate or blood pressure. In conclusion, repeated bouts of IPC over seven consecutive days increased skeletal muscle oxidative capacity and microvascular muscle blood flow. These findings are consistent with enhanced mitochondrial and vascular function following repeated IPC and may be of clinical or sporting interest to enhance or offset reductions in muscle oxidative capacity.